How Live TikTok Shopping Affects Brand Image and Purchase Intention among Consumers of YSL Beauty Luxury Products in Indonesia - Clara Agatha; Ahmadi Ahmadi; Nur Afifah; Ana Fitriana (Economics and Digital Business Review, 2026)
Study This analyze The influence of Live Streaming, Social Media Influencers, and Electronic Word of Mouth ( eWOM ) on Purchase Intention with Brand Image as an variables mediation among YSL Beauty Indonesia consumers on the TikTok platform. Research results show that Live Streaming has an effect significant towards Purchase Intention, however No influential significant on Brand Image, so its influence nature directly . On the other hand , Social Media Influencers and eWOM proven influential positive and significant on Brand Image and Purchase Intention. In addition , Brand Image has an influence significant on Purchase Intention and plays a role as a mediator in the influence of Social Media Influencers and eWOM , but No mediate The influence of live streaming. Research methods use approach quantitative with survey against 150 respondents users active Live TikTok Shopping YSL Beauty and analyzed using SEM-PLS. Findings This confirm that in context product luxury cosmetics , communication strategy based credibility social and experience consumer more effective in build image brand compared to promotion interactive term short .